2020
DOI: 10.3390/agriculture10060238
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Salt Concentration on the Mineral Nutrition of Tetragonia tetragonioides

Abstract: The purpose of the experiment was to study the effect of salinity (NaCl) on growth, biomass production (total yield), mineral composition (macro- and micronutrient contents in leaves and the soil in which the plant is grown) of Tetragonia tetragonioides during the vegetation period. The experimental work was conducted in the greenhouse at the University of Lille 1, France, from 2 November 2015 to 25 January 2016. Three salinity treatments (T1 (50 mM NaCl), T2 (100 mM NaCl), T3 (200 mM NaCl)) and a control trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Numerous reports have already been published on the diversity of salt-tolerant plant beneficial bacteria, including various species belonging to Acetobacter , Azospirillum , Arthrobacter , Bacillus , Pseudomonas , Rhizobium , Serratia , and Steretrophomonas [ 27 , 28 ]. They preferentially colonize the root system rich in nutrients due to exudates and form beneficial associations with the plants [ 10 , 22 , 29 ]. These microbes adopted various drought and salt stress strategies through several physiological acclimation mechanisms [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reports have already been published on the diversity of salt-tolerant plant beneficial bacteria, including various species belonging to Acetobacter , Azospirillum , Arthrobacter , Bacillus , Pseudomonas , Rhizobium , Serratia , and Steretrophomonas [ 27 , 28 ]. They preferentially colonize the root system rich in nutrients due to exudates and form beneficial associations with the plants [ 10 , 22 , 29 ]. These microbes adopted various drought and salt stress strategies through several physiological acclimation mechanisms [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…New Zealand spinach is also consumed as a vegetable or in salads and used for medicinal purposes [ 21 ]. Bekmirzaev et al [ 22 ] observed a salt tolerance of T. tetragonioides up to 200 mM NaCl and a high potential for removing sodium ions from the soil. Although several studies on growth, salt tolerance, and physiological traits of Tetragonia tetragonioides were already published, knowledge about endophytes or rhizobacteria associated with New Zealand spinach and their role in plant stress tolerance is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…Growth retardation and the loss of fresh and dry weights from stems and leaves of plants under salinity stress have been observed in previous studies [45][46][47]. In addition, based on fresh and dry weights, it has been demonstrated in several studies that the shoot ratios of many plants increase under salinity stress [44,48,49].…”
Section: Discussionmentioning
confidence: 53%
“…In the second irrigation event, we observed that the electrical conductivity of the drainage water (EC w ) increased relative to that in the first irrigation event, then decreased steadily with further irrigation events. This can be attributed, first, to the assimilation of salts in the soil by salt-tolerant plants [38][39][40][41][42] and, second, to the process of salt leaching from the soil by irrigation [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…According to a report in 2020, nearly 800 million hectares of land have been faced with saline problems [2]. Unfortunately, it is predicted that salinity will continue to spread to other parts of the world in the near future as a consequence of climate change and inappropriate farming practices [3]. It is known that under stress conditions, various biological processes in plants are negatively affected, including reduction in shoot growth, photosynthesis and biomass accumulation; promotion of senescence; and decrease in seed quantity and quality [4][5][6].…”
Section: Introductionmentioning
confidence: 99%